Immunotoxicity assessment of multiwalled carbon nanotubes following whole-body inhalation exposure for 30 and 90 days in B6C3F1/N mice and 30 days in HSD:Harlan Sprague Dawley SD® rats - Johnson, Victor J.; Walker, Nigel J.; Luster, Michael I.; Burleson, Gary R.; Cora, Michelle; Baker, Gregory L.; Sparrow, Barney; Germolec, Dori R. (Frontiers in Toxicology, 2025)
BackgroundSeveral lines of evidence suggest the possibility that inhalation exposure to multi-walled carbon nanotubes (MWCNT) at occupationally relevant doses can lead to systemic immunotoxicity. To test this hypothesis, we undertook in-depth examination of immune function in mice and rats exposed by inhalation to relatively low levels of 1020 Long Multiwalled Carbon Nanotubes (L-MWNT-1020).MethodsStudies were conducted to determine the systemic and pulmonary immunotoxic effects in mice and rats exposed to L-MWNT-1020 following whole-body inhalation for 6 h/day for 5 days/week for 30 (mice and rats) and 90 (mice) days at dose levels of 0, 0.06, 0.2, and 0.6 mg/m3. Additional groups were administered cyclophosphamide (CPS) as a positive control for each cohort. Following exposure, pulmonary macrophage phagocytosis, immunophenotypic analysis of immune cells populations in the spleen, and systemic immune function, including tests for humoral (T-dependent antibody response, TDAR), cell-mediated (cytotoxic T-lymphocyte [CTL] activity), and innate (Natural Killer [NK] cell activity) immunity were conducted.ResultsWhile exposure increased pulmonary macrophage activity, no major changes were observed in any of the systemic immune parameters measured in mice exposed for 30 or 90 days. In rats, there was a slight decrease in humoral immunity coinciding with an increase in the number of splenic T cell and NK cell populations.ConclusionAlthough pulmonary macrophage activity increased in mice following exposure to L-MWNT-1020, systemic immune function for the most part remained unaffected. In contrast, rats demonstrated a slight decrease in humoral immune function as well as an increase in spleen cell numbers, T cell, and NK cell populations suggesting species-specific effects on systemic immunity, however, these effects were small and their biological significance with respect to altering disease susceptibility is unclear.